The survey of planetary nebulae in Andromeda (M31) – IV. Radial oxygen and argon abundance gradients of the thin and thicker disc. Issue 2 (24th September 2022) - Bhattacharya, Souradeep; Arnaboldi, Magda; Caldwell, Nelson; Gerhard, Ortwin; Kobayashi, Chiaki; Hartke, Johanna; Freeman, Kenneth C; McConnachie, Alan W; Guhathakurta, Puragra
ABSTRACT: We obtain a magnitude-limited sample of Andromeda (M 31) disc PNe with chemical abundance estimated through the direct detection of the [O iii ] 4363 Å line. This leads to 205 and 200 PNe with oxygen and argon abundances, respectively. We find that high- and low-extinction M 31 disc PNe have statistically distinct argon and oxygen abundance distributions. In the radial range of 2−30 kpc, the older low-extinction disc PNe are metal-poorer on average with a slightly positive radial oxygen abundance gradient (0.006 ± 0.003 dex kpc −1 ) and slightly negative for argon (−0.005 ± 0.003 dex kpc −1 ), while the younger high-extinction disc PNe are metal-richer on average with steeper radial abundance gradients for both oxygen (−0.013 ± 0.006 dex kpc −1 ) and argon (−0.018 ± 0.006 dex kpc −1 ), similar to the gradients computed for the M 31 H ii regions. The M 31 disc abundance gradients are consistent with values computed from major merger simulations, with the majority of the low-extinction PNe being the older pre-merger disc stars in the thicker disc, and the majority of the high-extinction PNe being younger stars in the thin disc, formed during and after the merger event. The chemical abundance of the M 31 thicker disc has been radially homogenized because of the major merger. Accounting for disc scale lengths, the positive radial oxygen abundance gradient of the M 31 thicker disc is in sharp contrast to the negative one of the MW thick disc. However, the thin discs of the MW and M 31 have remarkably similar negative oxygen abundance gradients.